Public Participation by Resident Associations in Local Authorities Administration in Kuching District, Sarawak, Malaysia - Ahi, Sarok; Leha, Saliman (The Social Science Learning Education Journal (SSLEJ), 2017)
The purpose of this article is to discussÂ public participations by Residents AssociationÂ in local authorities administration in Kuching District, Sarawak, Malaysia. This article also discusses the structure of the Resident Associations and the various activities these structures organised which benefitted the communities living in the neighbourhood. All three local authorities Â namely the DBKU, MBKS and MPP indicated that Resident Associations Â play an important role to create mutual relationship with the public towards better local authorities administration. Â In addition, it highlighted theÂ roles played by the Resident Associations inÂ three local in promoting public participation through variousÂ programmes and activities. Â Â Resident Associations also play an important in preventing crimes by improving security at their neighbourhood, increasing vigilance, creating and maintaining a caring community.Â They also play a vital part in the local government administration especially in maintaining cordial relationship between the residents and the local authorities. Finally this article discuss the programmes and activities implemented by the Resident Associations in collaboration with the local authorities. Amongst the activities discussed in this article are safety and crime prevention programmes, recycling programme, recreational and sports activities, communityÂ services or gotong-royong, and other programmes that are beneficial to communities living in the neighbourhood.